Perjanjian Kerjasama Jasa Operator Yang Aman Dan Menjamin Kepastian Hukum Di Bidang Transportasi - Anggriani, Reni (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2015)
A success in the business world could be seen one from the absence of problems nor disputes among the business people.The interests of investors either business people in conducting business transaction caused by the availability of a certainty within the business itself. The investor or business people would be interested to conduct a business or transaction with the result that there are teasing and ensure legal certainty in the position of conducting business or cooperation in these efforts. Perhaps even legal certainty is a major factor which is very important for them to conduct business, especially a business or partnership that has a very large nominal value, including the cooperation in transportation sector, especially the service provider. Legal certainty is a major factor to gain the trust and convince the investors to do a partnership in conducting business transactions. One of kinds of legal certaintycould be stated in a written agreement in which regulates everything that had been agreed upon by the parties who enter into agreement. The cooperation of operator services in transportation sector actually has usually conducted even though several of them conducted without a clear agreement between the rights and obligations of the parties, that when there is damage to the armadas for example if it is not agreed in advance, the parties who will bear the cost of the damage that will refuse the responsibility.Likewise, the method of payment to be clear on how and what if there is a delay or no increase in the price of fuel the vehicle or if there is inflation is going to affect the implementation of on going cooperation agreement. Moreover if all that does not set out clearly and firmly Â will lead to problems that will result in performance.